1987
DOI: 10.1002/ajmg.1320260119
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile hyaline fibromatosis: Two new patients and review of the literature

Abstract: We report on a sister and a brother (born to normal consanguineous parents) with joint contractures and osteolytic lesions of bones. The sister had also gingival hyperplasia and skin lesions consisting of multiple tumors of the face, nose, palate, ears, and neck. Histologic examination showed findings of juvenile hyaline fibromatosis. The literature is reviewed, and 15 cases already reported are summarized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
5

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 21 publications
1
44
0
5
Order By: Relevance
“…First mentioned by Murray in 1873 as``molluscum ®brosum'', Kitano et al [1972] introduced the term`j uvenile hyaline ®bromatosis'' in 1972. Since then, several reports have appeared [Remberger et al, 1985;Fayad et al, 1987;Kan and Rogers, 1989;O'Neill and Kasser, 1989]. Patients with JHF also have joint contractures, nodular skin lesions, which can grow into tumors of several centimeter diameter, gingival hypertrophy, and generalized osteopenia.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…First mentioned by Murray in 1873 as``molluscum ®brosum'', Kitano et al [1972] introduced the term`j uvenile hyaline ®bromatosis'' in 1972. Since then, several reports have appeared [Remberger et al, 1985;Fayad et al, 1987;Kan and Rogers, 1989;O'Neill and Kasser, 1989]. Patients with JHF also have joint contractures, nodular skin lesions, which can grow into tumors of several centimeter diameter, gingival hypertrophy, and generalized osteopenia.…”
Section: Introductionmentioning
confidence: 98%
“…Similar to ISH, the mental development is normal. It is possible that ISH and JHF are based on the same pathological process, the former being a more severe form with early onset and death in infancy and the latter being the milder variant with a later onset and survival into adulthood [Remberger et al, 1985;Fayad et al, 1987;Kan and Rogers, 1989;O'Neill and Kasser, 1989;Mancini et al, 1999], but this remains speculative.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation of amorphous, hyaline material has been recognized in two clinically distinct syndromes: infantile systemic hyalinosis (ISH) [3, 4, 5]and juvenile hyaline fibromatosis (JHF) [6, 7, 8, 9, 10, 11, 12, 13]. Clinically these disorders can be either limited to hyaline deposition in the skin and bone or may involve viscera to various degrees of severity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that ISH has a very poor prognosis since it results in death within the first two years of life (2,25,26). Both studied cases died by the age of two years due to recurrent respiratory infections.…”
Section: Discussionmentioning
confidence: 84%